Occurrence and significance of coumarin in cachaça stored in amburana (Research, Society and Development, 2023)
Coumarin (1,2-benzopyrone) is a phenolic compound of vegetal origin. Beside its wide use in human medicine, it is also used as an odorant in food, beverages, cosmetics and perfumery, and as a bioactive component in nutraceutical foods. However, due to the risk of hepatotoxicity and other adverse effects in more sensitive people, international health agencies recommend a limit of 0.1 mg/kg/day for daily intake. Following a worldwide trend, Brazilian legislation recently established a limit of 10 mg/kg for coumarin in alcoholic beverages. With the aim of investigating the level of compliance of cachaça stored in amburana to the established limit, the coumarin content in twelve commercial cachaças, whose labels inform storage in amburana, was analyzed. The average result was above the established value, pointing to the need for monitoring and control. Given the diversity of Brazilian woods, there was a warning sign for cachaça to be stored exclusively in barrels of well-characterized species within the extractive fraction.